2017
DOI: 10.18632/oncotarget.14640
|View full text |Cite
|
Sign up to set email alerts
|

Metformin promotes apoptosis in hepatocellular carcinoma through the CEBPD-induced autophagy pathway

Abstract: Metformin, as an AMP-activated protein kinase (AMPK) activator, can activate autophagy. A study showed that metformin decreased the risk of hepatocellular carcinoma (HCC) in diabetic patients. However, the detailed mechanism in the metformin-mediated anticancer effect remains an open question. Transcription factor CCAAT/enhancer-binding protein delta (CEBPD) has been suggested to serve as a tumor suppressor and is responsive to multiple anticancer drugs in HCC. In this study, we found that CEBPD and autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 64 publications
0
53
0
Order By: Relevance
“…8,41 This surprising and difficult to understand discrepancy probably relies on the effect of selection biases and confounding factors on results. Therefore, future studies on this topic should take into account, for instance, insulin and hypoglycaemic drugs (in particular metformin that seems to have strong antineoplastic effects 42,43 ) as factors potentially capable to influence results. This study presents some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…8,41 This surprising and difficult to understand discrepancy probably relies on the effect of selection biases and confounding factors on results. Therefore, future studies on this topic should take into account, for instance, insulin and hypoglycaemic drugs (in particular metformin that seems to have strong antineoplastic effects 42,43 ) as factors potentially capable to influence results. This study presents some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism and inflammation may not be the only pathomechanisms affected by metformin/NRF2. In fact, other salutary effects have been described for redox (Kocer et al, 2014;Kelleni et al, 2015) and protein homeostasis (Tsai et al, 2017).…”
Section: E Repurposing Instead Of De Novo Drug Discovery and Developmentioning
confidence: 99%
“…For instance, an epidemiologic analysis revealed an association between metformin, a first‐line medication for the treatment of type 2 diabetes (T2DM), and a reduced risk of HCC development . Basic studies revealed that metformin inhibited HCC cell proliferation, invasion and angiogenesis and induced both apoptosis and autophagy through AMP‐activated protein kinase (AMPK) ‐dependent and ‐independent pathways . In addition, dipeptidyl peptidase 4 inhibitors (DPP4‐Is), which have been developed as a viable option for T2DM therapy, can enhance tumor immunity by stabilizing biologically active forms of C‐X‐C motif chemokine 10 and may thus yield potential therapeutic benefits for cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…6 Basic studies revealed that metformin inhibited HCC cell proliferation, invasion and angiogenesis and induced both apoptosis and autophagy through AMP-activated protein kinase (AMPK) -dependent and -independent pathways. 7,8 In addition, dipeptidyl peptidase 4 inhibitors (DPP4-Is), which have been developed as a viable option for T2DM therapy, can enhance tumor immunity by stabilizing biologically active forms of C-X-C motif chemokine 10 and may thus yield potential therapeutic benefits for cancer patients. 9 Our recent study also revealed that DPP4-I exerted preventive effects against murine hepatocarcinogenesis via antiangiogenic and antioxidative activities.…”
Section: Introductionmentioning
confidence: 99%